2021
DOI: 10.14814/phy2.14713
|View full text |Cite
|
Sign up to set email alerts
|

Stress hyperglycemia, cardiac glucotoxicity, and critically ill patient outcomes current clinical and pathophysiological evidence

Abstract: Stress hyperglycemia describes a state of blood glucose deregulation that occurs during a period of acute physiological stress (Dungan et al., 2009; Marik & Bellomo, 2013). It is defined as an episode of hyperglycemia that resolves spontaneously after the dissipation of the acute illness (Dungan et al., 2009). Stress hyperglycemia is characteristically transient and is frequently observed in critically ill patients. Its presence has, however, been positively correlated with ICU mortality. Indeed, several studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 187 publications
1
22
0
Order By: Relevance
“…An increase in SOD gene expression in the diabetic group was found compared with the other groups ( Figure 3 A), suggesting an increase in antioxidants as an attempt to protect the retinal cells from oxidative stress caused by hyperglycemia. This result is consistent with a study that concluded that the growth of SOD in the diabetic group may be related to a higher glucose intercellular concentration that activates the hexosamine metabolism and aldose reductase paths, resulting from ROS increase [ 54 ]. MitoTEMPOL may also modulate antioxidant levels as it efficiently inhibited mitochondrial superoxide generation in high-glucose-stimulated cardiomyocytes, and its administration may have reduced the antioxidant levels and have therapeutic benefit in diabetic cardiac complications [ 18 ].…”
Section: Discussionsupporting
confidence: 92%
“…An increase in SOD gene expression in the diabetic group was found compared with the other groups ( Figure 3 A), suggesting an increase in antioxidants as an attempt to protect the retinal cells from oxidative stress caused by hyperglycemia. This result is consistent with a study that concluded that the growth of SOD in the diabetic group may be related to a higher glucose intercellular concentration that activates the hexosamine metabolism and aldose reductase paths, resulting from ROS increase [ 54 ]. MitoTEMPOL may also modulate antioxidant levels as it efficiently inhibited mitochondrial superoxide generation in high-glucose-stimulated cardiomyocytes, and its administration may have reduced the antioxidant levels and have therapeutic benefit in diabetic cardiac complications [ 18 ].…”
Section: Discussionsupporting
confidence: 92%
“…Another relevant observation was the development of hyperglycemia that occurred at CO 2 concentrations of 10% and higher. Hyperglycemia is a sign of severe stress and is also observed during hemorrhagic shock and critical illness, and is related to sympathoadrenergic activity ( Marik and Bellomo, 2013 ; Scheen et al, 2021 ). Importantly, hyperglycemia is related to poor outcome in critical illness ( Scheen et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Percent DPPH inhibition activity in the pancreas of normal control group (75.55 ± 3.12) was significantly (### p < 0.001) high as compared to diabetic control group (22.41 ± 4.25). % DPPH inhibition activity of glibenclamide and morin (2,5,10,15,30, and 50 µg/kg body weight) treated groups in the pancreas tissues were 49.88 ± 3.21 **, 52.66 ± 2.81 **, 60.42 ± 2.12 ***, 65.33 ± 22.13 ***, 69.33 ± 3.12 ***, and 71.42 ± 3.23 *** which were significantly higher than that of diabetic control group.…”
Section: Effect Of Various Treatments On Intracellular Ros Levelmentioning
confidence: 99%
“…Chronic hyperglycemia results in increased ROS production through increased oxygen consumption, disruption in mitochondrial function, or activation of ROS-producing enzymes. The overproduction of ROS or reduced activity of endogenous antioxidants results in oxidative stress that seems to be due to an imbalance between the oxidizing species as mentioned before, resulting in oxidative stress and cellular death [ 5 ].…”
Section: Introductionmentioning
confidence: 99%